2015
DOI: 10.1055/s-0035-1554721
|View full text |Cite
|
Sign up to set email alerts
|

Medical Treatment of Graves’ Orbitopathy

Abstract: The medical treatment of Graves? orbitopathy (GO) is usually reserved to moderate to severe disease. Steroids have been widely employed and possess anti-inflammatory activity, but about 20?30% of patients are not responsive and about 20% present with disease recurrence. Immunosuppressive therapy alternative to corticosteroids may target the different antigens involved in pathogenic mechanisms of GO. Some have already been employed in clinical studies and showed interesting results, although the lack of randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 110 publications
1
31
0
2
Order By: Relevance
“…The rationale for using RTX in GO is the potential blockade of pathogenic autoantibody generation and production of inflammatory cytokines or the depletion of B cells as antigen-presenting cells. Data recently published showed a significantly different efficacy maybe due to a different disease duration and severity of patients recruited, that means a different inflammatory pattern [48].…”
Section:  Humoral Factorsmentioning
confidence: 99%
“…The rationale for using RTX in GO is the potential blockade of pathogenic autoantibody generation and production of inflammatory cytokines or the depletion of B cells as antigen-presenting cells. Data recently published showed a significantly different efficacy maybe due to a different disease duration and severity of patients recruited, that means a different inflammatory pattern [48].…”
Section:  Humoral Factorsmentioning
confidence: 99%
“…The aim of treatment is to suppress orbital inflammation and reduce consequent tissue remodelling in extraocular muscles, orbital fat and other periocular soft tissues (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…While the classic essential nutrients have been widely evaluated, there is also great interest in selenium supplementation in relation to MetS. The beneficial effects of selenium on reducing CVD mortality [6], and maintenance of overall health, especially for the thyroid, immunity and homeostasis [7][8][9][10] have been previously reported. In a study by Wang et al [11], a positive association between selenium concentration and T2DM reported in people with relatively low and/or high selenium concentrations.…”
Section: Introductionmentioning
confidence: 99%